Assessment of the environmental toxicity and carcinogenicity of tungsten-based shot. - Thomas, Vernon G.; Roberts, Michael J.; Harrison, Paul T. C. (Elsevier, 2009)
The toxicity of elemental tungsten released from discharged shot was assessed against previous studies that established a 1% toxic threshold for soil organisms. Extremely heavy theoretical shot loadings of 69,000 shot/ha were used to generate estimated environmental concentrations (EEC) for two brands of tungsten-based shot containing 51% and 95% tungsten. The corresponding tungsten EEC values were 6.5–13.5 mg W/kg soil, far below the 1% toxic threshold. The same shot loading in water produced tungsten EEC values of 2.1–4.4 mg W/L, levels that are not toxic under experimental conditions. Pure tungsten has not been shown to exhibit carcinogenic properties when ingested or embedded in animal tissues, but nickel, with which it is often alloyed, has known carcinogenicity. Given the large number of waterfowl that carry shot embedded in their body, it is advisable to screen lead shot substitutes for their carcinogenic potential through intra-muscular implantation.
Keywords: Tungsten; Alloys; Environmental toxicity; Carcinogenicity; Shot